Assessing McCallum and Taylor rules in a cross-section of emerging market economies - Aaron Mehrotra; José R. Sánchez-Fung (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
The paper estimates McCallum and Taylor monetary policy reaction functions, and hybrids mixing instruments and targets from the two frameworks, for 20 emerging market economies. McCallum-Taylor specifications with an interest rate instrument and a nominal income gap target perform better than benchmark Taylor rules in describing monetary policy in inflation targeting economies. Estimating reaction functions for economies operating monetary and exchange rate targeting regimes produces mixed results, often revealing a lean with the wind behaviour. Instrument smoothing is a feature in the monetary base and in the interest rate reaction functions, but the exchange rate is not consistently significant. The results from the econometric analysis are robust to using alternative estimators.
URN:NBN:fi:bof-201408071902
Keywords: E52; E58; F41; 330; McCallum and Taylor rules; nominal feedback rule; monetary policy; inflation targeting; emerging markets